Gut microbiome composition: link between sports performance and protein absorption? - Péter Fritz; Réka Fritz; Pál Bóday; Ádám Bóday; Emese Bató; Péter Kesserű; Csilla Oláh (Taylor & Francis Group, 2024)
ABSTRACTBackground Sufficient protein intake is essential for adequate physical condition and athletic performance. However, numerous factors can influence the absorption of consumed protein, including timing, type of protein intake, and gut microbiota. In the present study, elite male water polo players consumed a plant-based, vegan protein supplement with (n = 10) or without (n = 10) pre- and probiotics daily during the 31-day study period.Methods We determined the anthropometric characteristics and body composition, dietary habits, gut microbiota composition, and blood parameters of the players at the beginning and at the end of the study. Body composition parameters were analyzed using the InBody 970 bioimpedance analyzer. Gut microbiome composition was determined from stool samples by metagenome sequencing. Paired and unpaired t-tests were used to determine differences between body composition and blood parameters within the groups and between the two groups at the two different sampling times. The Wilcoxon test was used to determine the change in bacterial composition during the study. Correlations between changes in body composition, blood parameters, and taxonomic groups were analyzed using a linear correlation calculation.Results Skeletal muscle mass (p < 0.001), body cell mass (p = 0.002), arm circumference (p = 0.003), and protein mass (p < 0.001) increased, while body fat mass (p = 0.004) decreased significantly in the intervention group which consumed pre- and probiotics in addition to protein supplement. Activated acetate (reductive TCA cycle I) and propionate (pyruvate fermentation to propanoate I) pathways correlated positively with increased skeletal muscle mass (p < 0.01 and p < 0.05), and the relative abundance of butyrate-producing species showed a significant positive correlation with changes in body fat mass in the intervention group (p < 0.05). These correlations were not observed in the control group without the intake of pre- and probiotics.Conclusions The composition of the gut microbiota may influence protein absorption and therefore body composition and consequently physical condition and sports performance.